Pengaruh Self-Expressive Brand, Brand Attachment dan Brand Trust terhadap Brand Advocacy yang dimediasi oleh Brand Love Customer Buttonscarves - Aldisa, Bunayya; Yunus, Mukhlis (Syiah Kuala University Press, 2024)
This research aims to measure the influence of Self-Expressive Brand, Brand Attachment, and Brand Trust on Brand Advocacy mediated by Brand Love on Buttonscarves product users in Banda Aceh City. The sample used in this research consisted of 130 respondents who are Buttonscarves customers in Banda Aceh City. Data collection in this research was distributing of questionnaire. The sampling technique used was purposive sampling. Structural Equation Modeling (SEM) was used as the analysis method to determine the influence among the variables involved. Based on the results of the statistical description, it was identified that the Self-Expressive Brand, Brand Attachment, Brand Trust, Brand Advocacy and Brand Love of Buttonscarves users in Banda Aceh City were already good. Based on the results of SEM analysis, Brand Love has effect on Brand Advocacy, Self-Expressive Brand effect on Brand Advocacy, Brand Attachment has effect on Brand Advocacy, Brand Trust has effect on Brand Advocacy, Self-Expressive Brand has effect on Brand Love, Brand Attachment has effect on Brand Love, Brand Trust has effect on Brand Love. Furthermore, based on the results of the Sobel test, it was found that Brand Love partially mediates the influence of Self-Expressive Brand, Brand Attachment, and Brand Trust on Brand Advocacy.